pH Shift Solubilization and Precipitation Protein Extraction from the Wastes of the Threadfin Bream, Nemipterus japonicus (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
This study aimed at extraction of protein from the wastes of the threadfin bream, Nemipterus japonicus using pH shift solubilization and precipitation processes and evaluation of the influencing factors on protein extraction. Towards this objective, the wastes of head, skin and internal organs were collected, and their nutritional composition evaluated. Furthermore, the ratio of waste: water for protein extraction was screened and the effect of pH, centrifugation speed and time on protein solubility rate, the amino acid composition and the molecular weight of proteins via SDS-PAGE were determined. Results demonstrated that moisture was the highest percentage (~70-78%) of all wastes. Highest protein content (19.67±1.10%), fat content (1.81±0.09%) and carbohydrate content (4.43±0.23%) were observed in skin, head and internal organs, respectively. The optimum ratio of waste: water for protein extraction is 1:9 for head, 1:8 for internal organs and 1:6 for skin. The protein extraction efficiency for all three samples were high at pH 3 and pH 12. Protein solubility increased with increased centrifugation speed up to 10,000 ×g, and there was no significant difference (P>0.05) between the protein solubility at 10,000 ×g and 20’000 ×g. Furthermore, there was significant difference (P
Keywords: Waste; solubilisation; precipitation; protein; pH-shift process